Findings From A Us State Department Of Health Workforce Assessment Survey - Brian C. Martin; Billy Brooks; Paula Masters; Robert Pack (European Scientific Journal, ESJ, 2016)
To determine the level of public health competency and training in the existing Tennessee Department of Health (TDH) workforce, an anonymous survey was implemented electronically. Questions were based on the Council on Linkages Core Public Health Competencies, a consensus set of skills identified by the Council on Linkages Between Academia and Public Health Practice as being desirable for the delivery of the Essential Public Health Services. All 5,178 active TDH employees were eligible to participate in the survey. In each of the core competency areas Leadership Level respondents scored consistently higher than Management Level or Entry Level, and Management Level respondents scored higher than Entry Level respondents. However, overall findings indicate that the eight core competency areas are not fully integrated into the TDH, and that there are clear training needs with high priority. Needs scores were calculated by dichotomizing responses into ‘Unaware/Aware’ and ‘Knowledgeable/Proficient’, with the ‘Unaware/Aware’ category indicating a training need in that area. When considering responses from all three Tiers, needs scores greater than 50% were found for six of the eight core competency areas. These results identify opportunities for improvements through a coordinated training strategy. Findings also highlight the need for deliberate planning activities related to diversity and hiring, as a significant percentage of employees are predicted to retire in the near future. Given resource constraints within TDH, training activities should be directed to increase competencies that are likely to have the greatest impact on the mission of the Department of Health.